THE ETHICS OF ENTREPRENEURSHIP IN ISLAM: AN ANALYSIS OF IJTIHAD AND THE PRACTICE OF INNOVATION - Masnih Mustapa; Siti Saidatulakmal Arishin, (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
Entrepreneurship is gaining importance in Muslim-majority countries, but its ethical implications in Islam have been understudied. This qualitative research analyzes existing literature and Islamic teachings to explore the ethics of entrepreneurship in Islam. The study focuses on the role of ijtihad in guiding ethical decision-making, the importance of innovation and social responsibility, and the influence of social and cultural factors on ethical considerations. The findings highlight the importance of ijtihad, innovation, and social responsibility in Islamic entrepreneurship and emphasize the need for a context-specific approach to ethical considerations. This research provides insights into the intersection of religious and economic values and their impact on entrepreneurship practices and calls for greater collaboration to develop ethical frameworks to support entrepreneurship in Muslim-majority contexts.